Synergy Between Chemical And Mechanical Actions In The Alkaline Peroxide Pulping Of Oil Palm Empty Fruit Bunch - Derma Wan, Yunita Megasari (2014)
The synergy between chemical and mechanical actions in an alkaline peroxide pulping (app) system was applied for producing pulp and paper from oil palm empty fruit bunch (efb). In the app, both pulping and brightening process occurring as one process. This process was found appropriately undertaken for 40 minutes at 70°c. Softening and brightening of efb was found most effectively done by synergizing the strength of alkaline peroxide with mechanical fibrillation from two different andritz sprout bauer refiner blade patterns. Variation of the ap strength was done by increasing the alkali-to-peroxide ratio from 2:2.5%, 4:5% to a maximum of 8:10%. Apart from that, ap strength was also increased by applying ap impregnation in multiple stages. Applying these variations on efb and subjecting the ap-treated efb to subsequent refining indicated that refining effect could be intensified by plate d2a505. The effect was so tremendous that variation in chemical strength was to a certain extent masked/ruled out. The effect of increasing ap chemical strength was clearly delineated by refining with plate 12716, which depended more on chemical strength to produce adequate fibrillation.